Analysing picking errors in vision picking systems - Vidovič, Ela (Logistics and sustainable transport, 2020)
Vision picking empowers users with access to real-time digital order information, while freeing them from handheld radio frequency devices. The smart glasses, as an example of vision picking enabler, provide visual and voice cues to guide order pickers. The glasses mostly also have installed navigation features that can sense the order picker's position in the warehouse. This paper explores picking errors in vision systems with literature review and experimental work in laboratory environment. The results show the effectiveness of applying vision picking systems for the purposes of active error prevention, when they are compared to established methods, such as paper-picking and using cart mounted displays. A serious competitor to vision picking systems are pick-to-light systems. The strong advantage of vision picking system is that most of the errors are detected early in the process and not at the customer's site. The cost of fixing the error is thus minimal. Most errors consequently directly influence order picker's productivity in negative sense. Nonetheless, the distinctive feature of the system is extremely efficient error detection.
Keywords: error prevention; intralogistics; intralogistika; inventory management; komisionarjenje; order picking; pametna očala; preprečevanje napak; skladiščenje; skladiščno poslovanje; smart glasses; storage operations; upravljanje zalog; warehousing